2015
DOI: 10.1016/j.ypmed.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening among women ≥70years of age in the United States—A referral problem or patient choice

Abstract: Objective Clinical guidelines recommend that women with a history of adequate screening and not otherwise at high risk may discontinue cervical cancer screening after 65 years of age. However, screening remains common among US women over 65 years old. This study was conducted to examine whether overutilization was attributable to provider’s recommendation or patient choice. Method This cross-sectional study used data from 1752 female participants (70+ years) from the 2013 National Health Interview Survey (NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…28 Physician specialty was associated with low-value cancer screening, although findings varied by screening type. As observed previously, 15,29 higher odds of cervical and breast cancer low-value screening were found for visits to an obstetrician/gynecologist relative to family/general practice physicians. When considering breast cancer screening for patients aged ≥75 years, the American College of Obstetrics and Gynecology recommends a shared decision-making approach that takes into account the patient's health status and life expectancy.…”
Section: Discussionsupporting
confidence: 81%
“…28 Physician specialty was associated with low-value cancer screening, although findings varied by screening type. As observed previously, 15,29 higher odds of cervical and breast cancer low-value screening were found for visits to an obstetrician/gynecologist relative to family/general practice physicians. When considering breast cancer screening for patients aged ≥75 years, the American College of Obstetrics and Gynecology recommends a shared decision-making approach that takes into account the patient's health status and life expectancy.…”
Section: Discussionsupporting
confidence: 81%
“…Firstly, a strength of the research lies in having operationalized CCS overuse in a 2-fold manner. Apart from screening outside of the recommended age-range, which had already been established in the literature as an indicator of overuse, 14,17 this study has also addressed CCS overuse in terms of screening frequency at the population level, and combined both approaches. This 2-fold operationalization of overuse is an innovative approach in survey-based research, as it has only been previously included in research where data on individual health records were available.…”
Section: Discussionmentioning
confidence: 99%
“…4 In the first form of CCS overuse, women within screening-eligible age undergo CCS too frequently. [8][9][10][11][12][13] In the second form, past research had identified both women below the recommended age 14,15 and women above the recommended age [16][17][18] for screening. CCS overuse entails several detrimental aspects, such as low cost-effectiveness at population level, 4,19 heterogeneous quality, 20 psychological distress 21 and false positives due to over-diagnosis.…”
mentioning
confidence: 99%
“…We also included whether participants had visited an obstetrician/gynecologist (OB/GYN), a nurse practitioner/physician assistant/midwife, or other healthcare provider (e.g., general doctor, therapist, and medical specialist) in the past 12 months, as visiting an OB/ GYN was associated with Pap smear use. [20][21][22] We compared prevalence of Pap testing in the past 3 years or in the past year between vaccinated women and unvaccinated women from NHIS 2013 to 2015 and assessed the role of providers and patients in the initiation of Pap testing. We used Pap smear utilization in the past year as an outcome of interest, because this study aimed to examine the effect of providers' recommendations for Pap smears in the past year on uptake of Pap smear by vaccination status.…”
Section: Methodsmentioning
confidence: 99%
“…These include women who are recommended not to receive Pap testing, such as those over 65 years with adequate prior screening and no history of precancerous cervical lesions and those who have had a total hysterectomy for noncancerous conditions. 21,22 On the other hand, about 20%-25% of screening services are requested by the patients themselves among women. 21,22 In this study, we assessed differences in provider's recommendation for Pap testing and patient-initiated Pap testing between vaccinated and unvaccinated women, using data from the National Health Interview Survey (NHIS) 2013-2015.…”
Section: Introductionmentioning
confidence: 99%